Analysis of the Implementation of Cooks' Occupational Health and Safety Standards on Food Sanitation : JEL Classification: L83; J28; I18; L66; M54 - Anisa Ade Safitri; Margriet Puspa Dewi (Newinera Publisher, 2026)
Restaurant kitchens are high-risk work areas where Occupational Health and Safety (OHS) standards and food sanitation practices must be implemented consistently to prevent workplace accidents and food contamination. This study aims to analyze the implementation of OHS standards among cooks and their relationship with food sanitation practices at Bale La Zara Resto Palembang. A descriptive qualitative approach was employed, with data collected through non-participant observation, semi-structured interviews with seven kitchen staff members, and documentation. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings show that the implementation of OHS standards remains partial and inconsistent. Several problems were identified, including inadequate ventilation due to the absence of an exhaust hood, insufficient lighting, wet and slippery floors, ergonomic complaints, and inconsistent use of Personal Protective Equipment (PPE). Food sanitation practices were also not fully standardized, as indicated by the absence of structured sanitation training, routine health inspections, documented monitoring, and consistent PPE compliance. The study further reveals that OHS and food sanitation are closely interconnected because unsafe working conditions may reduce hygiene compliance and increase the risk of food contamination. Therefore, the restaurant needs to strengthen an integrated OHS and food sanitation system through written SOPs, regular training, facility improvement, routine health checks, daily monitoring checklists, and stricter PPE enforcement. These efforts are essential to build a stronger safety culture and ensure safer food handling practices in restaurant kitchen operations.